Bounding tractogram redundancy - Persson, Sanna; Moreno, Rodrigo (Frontiers in Neuroscience, 2024)
In tractography, redundancy poses a significant challenge, often resulting in tractograms that include anatomically implausible streamlines or those that fail to represent the brain's white matter architecture accurately. While current filtering methods aim to refine tractograms by addressing these issues, they lack a unified measure of redundancy and can be computationally demanding.We propose a novel framework to quantify tractogram redundancy based on filtering tractogram subsets without endorsing a specific filtering algorithm. Our approach defines redundancy based on the anatomical plausibility and diffusion signal representation of streamlines, establishing both lower and upper bounds for the number of false-positive streamlines and the tractogram redundancy. We apply this framework to tractograms from the Human Connectome Project, using geometrical plausibility and statistical methods informed by the streamline attributes and ensemble consensus. This work advances the understanding of tractogram redundancy and supports the refinement of tractography methods. Future efforts will focus on further validating the proposed framework and exploring tractogram compression possibilities.